Samarium Ions Doped Titania Photoelectrodes for Efficiency Influence of Dye-Sensitized Solar Cells. Issue 5 (27th January 2016) - Zhang, Zige; Cui, Zijian; Zhang, Kaiyue; Feng, Yaqing; Meng, Shuxian
Abstract : Samarium ions (Sm 3+ )-doped TiO2 photoelectrodes are used to enhance the photovoltaic efficiency of dye-sensitized solar cells (DSSCs). The improvments are especially exhibited in the visible light absorption, interface area and photocurrent density Jsc . Sm 3+ -doped samples are benefit to form a new microstructure and improve the electrolyte transfer. In comparison to different doping concentrations, optimized 0.05 g-Sm/TiO2 could achieve fill factor of 0.69 and efficiency of 7.23%. It is obviously better than the undoped-titania photoelectrodes. This enhancement is due to the improved UV radiation harvesting via a down-conversion luminescence process by the doped samarium ions.